RETRACTED ARTICLE: Comparative analysis of the Corynebacterium glutamicum transcriptome in response to changes in dissolved oxygen levels. (1st February 2017) - Liu, Xiuxia; Yang, Sun; Wang, Fen; Dai, Xiaofeng; Yang, Yankun; Bai, Zhonghu
Abstract: The dissolved oxygen (DO) level of a culture of Corynebacterium glutamicum ( C. glutamicum ) in a bioreactor has a significant impact on the cellular redox potential and the distribution of energy and metabolites. In this study, to gain a deeper understanding of the effects of DO on the metabolism of C. glutamicum, we sought to systematically explore the influence of different DO concentrations on genetic regulation and metabolism through transcriptomic analysis. The results revealed that after 20 h of fermentation, oxygen limitation enhanced the glucose metabolism, pyruvate metabolism and carbon overflow, and restricted NAD + availability. A high oxygen supply enhanced the TCA cycle and reduced glyoxylate metabolism. Several key genes involved in response of C. glutamicum to different oxygen concentrations were examined, which provided suggestions for target site modifications in developing optimized oxygen supply strategies. These data provided new insights into the relationship between oxygen supply and metabolism of C. glutamicum .